Characteristics of the Book Market Based on Scenarios of Environment Conditions - Czaplińska, Anna (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2020)
Books are the final product of the process, which consists of the phase of an individual or collective creative process, production phase implemented in the enterprises of the printing industry and the service phase consisting in the dissemination, distribution and commercialisation of the product. The whole process is therefore very complex due to its alternating intangible and material nature, which, apart from the economic dimension, also has a social dimension. Therefore, the product is highly sensitive to the processes occurring in the broad culture susceptible to national environmental influences determined by global processes. The goal of the work was a general description of the book market presented in a strategic perspective in the light of dynamic changes taking place in its environment. The use of the scenario method of environment conditions for analysing the book market was used to better identify the macro -environment components that can have a decisive impact on the functioning of the book market. Based on the results obtained, it seems that there will probably be a further increase in access to the texts, based on modern technologies. The key factor determining the further development of all links in the book market will be the socio -cultural factor, which is associated with the transition towards information society (hypertext) in which information itself and the convenient medium of its message are important.